2006
DOI: 10.1002/hlca.200690113
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Crystal Structures of Ammoniates with the Phenyl‐Substituted Polytin Anions Sn2Ph$\rm{_{\bf 4}^{{\bf 2} - } }$, cyclo‐Sn4Ph$\rm{_{\bf 4}^{{\bf 4} - } }$, and Sn6Ph$\rm{_{{\bf 12}}^{{\bf 2} - } }$

Abstract: The reaction of diphenyltin dichloride with the binary Zintl phase K4Sn9 in the presence of excess lithium and 18‐crown‐6 in liquid ammonia led to the ammoniate [K(18‐crown‐6)(NH3)2]2Sn2Ph4 (1). The analogous reaction with K4Ge9 and potassium in the absence of further alkali metal ligands resulted in the compound [K2(NH3)12]Sn6Ph12 ⋅ 4 NH3 (3). Cs6[Sn4Ph4](NH2)2 ⋅ 8 NH3 (2) was prepared by reacting diphenyltin dichloride with a surplus of caesium in liquid ammonia. The low‐temperature single‐crystal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…More recently, synthesis of substituted diaryldimethylstannanes was proposed to proceed via the intermediate Me 2 Sn 2− , but also formation of the dimeric species (Me 2 Sn) 2 2− was anticipated, since the dimer (PhMe 2 Sn) 2 emerged among the reaction products or (18-crown-6)diammine potassium counterions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, synthesis of substituted diaryldimethylstannanes was proposed to proceed via the intermediate Me 2 Sn 2− , but also formation of the dimeric species (Me 2 Sn) 2 2− was anticipated, since the dimer (PhMe 2 Sn) 2 emerged among the reaction products or (18-crown-6)diammine potassium counterions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the parent phenyl-substituted compound, crystal structures of the symmetric hexaaryldistannanes (p-Tol 3 Sn) 2 (Schneider-Koglin et al, 1991), (o-Tol 3 Sn) 2 (Schneider-Koglin et al, 1993), and [(C 6 F 5 ) 3 Sn] 2 (Bojan et al, 2010), and two co-crystalline compounds with included hexakis(2,6-diethylphenyl)distannane (Sita and Bickerstaff, 1989) and included {[o-(CH 2 NMe 2 )C 6 H 4 ] Ph 2 Sn} 2 (Turek et al, 2009), respectively, have been reported. The dianion Sn 2 Ph 4 2has been the subject of investigation in the context of phenyl-substituted Zintl anions of the heavier main-group elements (Scotti et al, 1997;Wiesler et al, 2006). To my knowledge, only for two solvates of (Ph 3 Sn) 2 singe-crystal X-ray structure determinations have so far been performed, i.e.…”
Section: C-h•••o and O-h•••π Interactionsmentioning
confidence: 99%